Basic study on mechanical vibration suppression system using 2-degree-of-freedom vibration analysis - Ikeda, Keigo; Kamimori, Kota; Kobayashi, Ikkei; Kuroda, Jumpei; Uchino, Daigo; Ogawa, Kazuki; Endo, Ayato; Kato, Taro; Liu, Xiaojun; Peeie, Mohamad Heerwan; Kato, Hideaki; Narita, Takayoshi (MDPI, 2023)
Mechanical vibrations adversely affect mechanical components, and in the worst case, lead to serious accidents by breaking themselves. To suppress vibrations, various studies have been conducted on vibration isolation, suppression, and resistance. In addition, technologies to actively suppress vibration have been rapidly developed in recent years, and it has been reported that vibrations can be suppressed with higher performance. However, these studies have been conducted mostly for low-order systems, and few studies have employed control models that consider the complex vibration characteristics of multi-degree-of-freedom (DOF) systems. This study is a basic study that establishes a control model for complex control systems, and the vibration characteristics of a 2-DOF system are calculated using the vibration analysis of a multi-DOF system. Furthermore, the vibration suppression performance of the 2-DOF system is investigated by performing vibration experiments.